AKHLAK DALAM PERSPEKTIF ISLAM DAN IMPLEMENTASINYA MENURUT PEDOMAN HIDUP ISLAMI WARGA MUHAMMADIYAH - Nadira; Risnawati HM; Abbas Baco Miro (STKIP Subang, 2026)
This study aims to provide a deeper understanding of the relationship between Islamic teachings and character building (Akhlak), as well as the implementation of these values within the Muhammadiyah perspective. The method used is library research by analyzing the Quran, Hadith, and the Guidelines for Islamic Living of Muhammadiyah Citizens (PHIWM). The results show that Akhlak is the fruit of Aqidah and Sharia which cannot be separated. In Muhammadiyah, Akhlak is not just a theory but a practice of life that covers vertical relationships with Allah and horizontal relationships with humans, oneself, the environment, and the state. Character building requires a long process through knowledge, habituation, and emulating the Prophet Muhammad SAW. Keywords: Akhlak, Islam, Muhammadiyah, Character Building